ALPPS Offers a Better Chance of Complete Resection in Patients with Primarily Unresectable Liver Tumors Compared with Conventional-Staged Hepatectomies: Results of a Multicenter Analysis - Schadde, Erik; Ardiles, Victoria; Slankamenac, Ksenija; Tschuor, Christoph; Sergeant, Gregory; Amacker, Nadja; Baumgart, Janine; Croome, Kris; Hernandez-Alejandro, Roberto; Lang, Hauke; de Santibaňes, Eduardo; Clavien, Pierre-Alain (World journal of surgery, 2014)
Background Portal vein occlusion to increase the size of the future liver remnant (FLR) is well established, using portal vein ligation (PVL) or embolization (PVE) followed by resection 4–8 weeks later. Associating liver partition with portal vein ligation for staged hepatectomy (ALPPS) combines PVL and complete parenchymal transection, followed by hepatectomy within 1–2 weeks. ALPPS has been recently introduced but remains controversial. We compare the ability of ALPPS versus PVE or PVL for complete tumor resection. Methods A retrospective review of all patients undergoing ALPPS or conventional staged hepatectomies using PVL or PVE at four high-volume HPB centres between 2003 and 2012 was performed. Patients with primary liver tumors and liver metastases were included. Primary endpoint was complete tumor resection. Secondary endpoints include 90-day mortality, complications, FLR increase, time to resection, and tumor recurrence. Results Forty-eight patients with ALPPS were compared with 83 patients with conventional-staged hepatectomies. Eighty-three percent (40/48 patients) of ALPPS patients achieved complete resection compared with 66 % (55/83 patients) in PVE/PVL (odds ratio 3.34, p = 0.027). Ninety-day mortality in ALPPS and PVE/PVL was 15 and 6 %, respectively ( p = 0.2). Extrapolated growth rate was 11 times higher in ALPPS (34.8 cc/day; interquartile range (IQR) 26–49) compared with PVE/PVL (3 cc/day; IQR2-6; p = 0.001). Tumor recurrence at 1 year was 54 versus 52 % for ALPPS and PVE/PVL, respectively ( p = 0.7). Conclusions This study provides evidence that ALPPS offers a better chance of complete resection in patients with primarily unresectable liver tumors at the cost of a high mortality. The technique is promising but should currently not be used outside of studies and registries.